Uso de las tic en la enseñanza-aprendizaje del idioma ingles a los estudiantes de II y III grado de la Escuela de Educación Básica Tarqui, cantón Puebloviejo, Provincia Los Ríos - Quinga Ramos, Sandy Genesis (2019)
The present research work is focused on explaining the influence of information and communication technologies (ICT) in the teaching-learning of the English language in the students of the II and III GRADE OF THE BASIC EDUCATION SCHOOL "TARQUI", CANTÓN PUEBLOVIEJO, LOS RÍOS PROVINCE. A set of activities was carried out using the basic theoretical concepts of information and communication technologies and language learning, a sample of 30 students of the II and III grade of the school of education were chosen to whom they were applied by means of the survey technique through a questionnaire. With the present investigation, it was possible to determine how the auxiliary means, resources and technological didactic influences influence the student's study in the teaching-learning of the English language in the students of the II and III cycle of the Tarqui Educational Unit of the Canton Pueblo Old, the results show that there is a positive correlation between the Tics and the teaching of the English language according to the Pearson coefficient. the realization of a methodology to improve the use of tics in the students of the Tarqui educational unit. It is proposed to implement technological tools to face the new ages in the use of the foreign language. Based on these priors, a didactic methodology is presented and described, for which it is essential to observe the needs that students present at the time of the use of technologies, general tools, specifically designed for teaching. This is an activity project designed to encourage motivation in the teaching-learning process of the English language that was carried out with students in II and III primary school. The English workshop uses the new methodologies (a virtual learning space) for teaching English in a fun and entertaining way